Extracellular Vesicles Derived From Platelets, Red Blood Cells, and Monocyte-Like Cells Differ Regarding Their Ability to Induce Factor XII-Dependent Thrombin Generation - Tripisciano, Carla; Weiss, René; Karuthedom George, Sobha; Fischer, Michael B.; Weber, Viktoria (Frontiers in Cell and Developmental Biology, 2020)
The discovery of genomic material as part of the cargo of extracellular vesicles (EVs) has paved the way to a new field of research and sparked tremendous interest in these sub-cellular structures, their roles as carriers of biologically active molecules, and their potential diagnostic and therapeutic applications. As transmitters of biological information, EVs contribute to physiological homeostasis and immunomodulation, but also have crucial roles in pathological conditions, such as tumorigenesis, inflammation, autoimmune disease, and thrombosis. The ability of EVs to support thrombin generation has been linked to their exposure of phosphatidylserine, an anionic phospholipid that is normally restricted to the inner leaflet of the plasma membrane, but exposed on the outer leaflet during EV biogenesis. Here, we investigated whether EVs derived from hematopoietic cell lineages (platelets and red blood cells) and from cell culture settings (monocytic cells) differ regarding their potential to support Factor XII-dependent thrombin generation. EVs were isolated from blood products or cell culture supernatants using differential centrifugation and characterized by a combination of flow cytometry, nanoparticle tracking analysis, and Western Blotting. Soluble factors co-enriched during the isolation of EVs were depleted from blood-cell derived EV fractions using size exclusion chromatography, while proteins bound to the surface of EVs were degraded by mild protease treatment. We found that platelet-derived and red blood cell-derived EVs supported Factor XII-dependent thrombin generation to comparable extents, while monocytic EVs failed to support thrombin generation when added to EV-depleted human plasma. We excluded a major contribution of co-enriched soluble proteins or of proteins bound to the EV surface to the thrombogenicity of blood cell-derived EVs. Our data suggest that the enhanced potential of blood cell-derived EVs to support thrombin generation is rather due to enhanced exposure of phosphatidylserine on the surface of blood cell-derived EVs. Extending these investigations to EVs from other cell types, such as mesenchymal stromal cells, will be crucial for their future therapeutic applications.